Urban forests and their contribution to sustainable urban development in a global context: a case study of Multan, Pakistan - Aleha, Anum; Zahra, Syeda Mahwish; Qureshi, Sabeen; Shah, Shehroze; Marri, Sohrab Ahmed; Khan, Maska (Frontiers in Climate, 2024)
Currently, cities and towns are home to over half of the global population, and this percentage will rise over the coming decades. Cities can be wonderful homes to live if planned and maintained properly, but most urban developments have noticeably caused environmental destruction, which in turn results in issues like urban heat islands, flooding, and air pollution. Cities require Forests as their breathing organs. The study refers to the case of Multan City, where the climate is deteriorating at an alarming rate due to rapid urbanization and the lack of vegetation. The study aims to provide an Urban Green Infrastructure (UGI), which abides by the key proactive resilience principles of effectiveness, diversity, dependence, durability, versatility, autonomy, planning, and adaptability. The strategic literature review has been done to study the effects of Urban Forests and various studies were reviewed as per methodology adopted worldwide. Policy frameworks of Sustainable Development Goals (SDG's) and New Urban Agenda (NUA) were considered while selecting sites for implementing Urban Forests. A five-point Likert scale questionnaire was developed for the participation of the community nearby. 10 different sites were selected in the city observing the ownership, and feasibility, irrespective of SDG, NUA and community opinions were considered. The study concludes with the design suggestion of one site as a prototype in the given context.